Fermented dairy product consumption and blood lipid levels in healthy adults: a systematic review - Yilmaz, Birsen; Alvanoudi, Panagiota; Kalogeropoulou, Aggeliki; Santa, Dushica; Bulmuş-Tüccar, Tuğçe; Nikolaou, Anastasios; Moreno-Indias, Isabel; Ruiz-Limon, Patricia; Gutiérrez-Repiso, Carolina; Hillesheim, Elaine; Meslier, Victoria; Mayo, Baltasar; et al. (Frontiers in Nutrition, 2025)
Cardiovascular diseases remain the leading cause of global mortality, with diet recognized as a key factor influencing cardiovascular risk biomarkers such as blood lipids. Emerging evidence suggests fermented dairy products may offer cardioprotective benefits via fermentation-derived bioactive metabolites. This systematic review, conducted within COST Action CA20218 Promoting Innovation of ferMENTed fOods (PIMENTO), evaluated the relationship between consumption of conventional fermented dairy products and blood lipid levels and cardiovascular diseases in healthy adults. Data were qualitatively summarized and synthesized narratively, following the European Food Safety Authority’s (EFSA) scientific guidance for health claim applications, including food characterization, bioavailability of relevant compounds, mechanisms of action, and safety. Sixty-eight studies were included: 14 controlled interventions (PICO), 37 non-controlled interventions (PIO), and 17 observational studies. Findings from intervention studies were largely inconsistent, with most trials reporting no significant changes in lipid markers following fermented dairy intake. However, a few studies reported modest reductions in total cholesterol and LDL-c or improved LDL/HDL ratios, particularly with yoghurt and kefir. Observational studies also yielded mixed and inconclusive results. Overall, study quality, result consistency, and mechanistic evidence were deemed “neither convincing nor sufficient” per EFSA criteria. Key limitations included high risk of bias, heterogeneous designs, inadequate product characterization, and limited mechanistic data. More rigorous, well-controlled human studies with appropriate comparators are needed to clarify whether conventional fermented dairy products have any lipid-lowering effects.Systematic review registrationosf.io/h2mbe/